2021
DOI: 10.1002/adom.202101963
|View full text |Cite
|
Sign up to set email alerts
|

Broadband Nonlinear Photoresponse and Ultrafast Carrier Dynamics of 2D PdSe2

Abstract: Palladium diselenide (PdSe2) exhibits considerable potential for application in broadband optoelectronic devices. In this work, the broadband nonlinear optical performance and ultrafast carrier dynamics from ultraviolet to near‐infrared of a trilayer PdSe2 are systematically studied. PdSe2 is found to achieve a giant saturable absorption performance. The modulation depth is 22.47% at 520 nm, whereas the nonsaturable loss and saturation intensity are only 3.83% and 15.47 GW cm−2, respectively, which are better … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 68 publications
3
20
0
Order By: Relevance
“…The intrinsic carrier density of PdSe 2 films with different thicknesses is obtained by THz-TDS, which is given in Figure S1. The initial surface carrier density of 15L PdSe 2 films is ∼2 × 10 13 cm –2 , and the pump fluences varying from 72 to 192 μJ/cm 2 correspond to carrier density change from 4.3 × 10 13 to 11.3 × 10 13 cm –2 , showing values similar to those reported in ref . The simulated fast and slow defect electron occupancy F f (left) and F s (right) as a function of delay time are given in Figure d.…”
supporting
confidence: 74%
See 1 more Smart Citation
“…The intrinsic carrier density of PdSe 2 films with different thicknesses is obtained by THz-TDS, which is given in Figure S1. The initial surface carrier density of 15L PdSe 2 films is ∼2 × 10 13 cm –2 , and the pump fluences varying from 72 to 192 μJ/cm 2 correspond to carrier density change from 4.3 × 10 13 to 11.3 × 10 13 cm –2 , showing values similar to those reported in ref . The simulated fast and slow defect electron occupancy F f (left) and F s (right) as a function of delay time are given in Figure d.…”
supporting
confidence: 74%
“…Moreover, through the use of ultrafast optical pump–probe spectroscopy, the layer-dependent interlayer breathing mode, and the longitudinal coherent acoustic phonon mode in PdSe 2 films have been studied, and the interlayer force constant and sound velocity were obtained in our previous study . In general, the carrier dynamics in PdSe 2 and other TMD films is conventionally described as defect capture. The detailed mechanisms, such as the roles of phonon, defect, and Auger process on the photocarriers, remain under debate and to be elucidated.…”
mentioning
confidence: 99%
“…Different forms of pentagonal PdSe 2 with a variable number of layers have been reported, possessing high stability in air, [18][19][20][21][22] which is an essential characteristic for their extended (long-term) use. Also, electrical transport characteristics, 23 remarkable optical, [24][25][26][27] and good thermoelectric properties 28 have been experimentally reported. On the theoretical side, several works have analyzed the physical properties of the material in its monolayer and multilayer forms.…”
Section: Introductionmentioning
confidence: 91%
“…Platinum diselenide (PtSe 2 ) is a recently emerging layered two-dimensional transition metal dichalcogenide (2D TMD), , exhibiting excellent physical properties such as high carrier mobility, , strong air stability, and intriguing spintronic and magnetic properties. , Also, bulk PtSe 2 is known as a type-II Dirac semimetal; thus, this material provides a platform for exploring novel quantum phenomena. The bandgap of PtSe 2 is zero in bulk, but it opens as the thickness decreases, becoming a semiconductor with a bandgap larger than 1 eV in the monolayer. Owing to this significant thickness dependence of bandgap and the above-mentioned outstanding physical properties, PtSe 2 has been demonstrated as a great material for thickness-engineered broadband photosensors, modulators, and saturable absorbers. The remarkable thickness dependence in PtSe 2 originates from strong coupling between layers resulting from covalent-like interlayer interactions. , Another consequence of the strong interlayer coupling is the pronounced interlayer phonon modes. Recent studies found that ultrafast laser excitation of PtSe 2 induces coherent phonons (CP) with large interlayer breathing force constants compared with other layered materials.…”
Section: Introductionmentioning
confidence: 99%